Effect of daily aspirin on risk of cancer metastasis: A study of incident cancers during randomised controlled trials - Rothwell, P; Wilson, M; Price, J; Belch, J; Meade, T; Mehta, Z (2012)
Background Daily aspirin reduces the long-term incidence of some adenocarcinomas, but effects on mortality due to some cancers appear after only a few years, suggesting that it might also reduce growth or metastasis. We established the frequency of distant metastasis in patients who developed cancer during trials of daily aspirin versus control. Methods Our analysis included all five large randomised trials of daily aspirin (≥75 mg daily) versus control for the prevention of vascular events in the UK. Electronic and paper records were reviewed for all patients with incident cancer. The effect of aspirin on risk of metastases at presentation or on subsequent follow-up (including post-trial follow-up of in-trial cancers) was stratified by tumour histology (adenocarcinoma vs other) and clinical characteristics. Findings Of 17 285 trial participants, 987 had a new solid cancer diagnosed during mean in-trial follow-up of 6?5 years (SD 2?0). Allocation to aspirin reduced risk of cancer with distant metastasis (all cancers, hazard ratio [HR] 0?64, 95% CI 0?48-0?84, p=0?001; adenocarcinoma, HR 0?54, 95% CI 0?38-0?77, p=0?0007; other solid cancers, HR 0?82, 95% CI 0?53-1?28, p=0?39), due mainly to a reduction in proportion of adenocarcinomas that had metastatic versus local disease (odds ratio 0?52, 95% CI 0?35-0?75, p=0?0006). Aspirin reduced risk of adenocarcinoma with metastasis at initial diagnosis (HR 0?69, 95% CI 0?50-0?95, p=0?02) and risk of metastasis on subsequent follow-up in patients without metastasis initially (HR 0?45, 95% CI 0?28-0?72, p=0?0009), particularly in patients with colorectal cancer (HR 0?26, 95% CI 0?11-0?57, p=0?0008) and in patients who remained on trial treatment up to or after diagnosis (HR 0?31, 95% CI 0?15-0?62, p=0?0009). Allocation to aspirin reduced death due to cancer in patients who developed adenocarcinoma, particularly in those without metastasis at diagnosis (HR 0?50, 95% CI 0?34-0?74, p=0?0006). Consequently, aspirin reduced the overall risk of fatal adenocarcinoma in the trial populations (HR 0?65, 95% CI 0?53-0?82, p=0?0002), but not the risk of other fatal cancers (HR 1?06, 95% CI 0?84-1?32, p=0?64; difference, p=0?003). Effects were independent of age and sex, but absolute benefit was greatest in smokers. A low-dose, slow-release formulation of aspirin designed to inhibit platelets but to have little systemic bioavailability was as effective as higher doses.